Analysis of Shoreline Changes Using the One-Line Model at Batu Karas Beach, Pangandaran, Indonesia - Subiyanto; Saqina Ramadhanti, Defania; Abdurrahman, Umar (International Journal of Global Operations Research, 2025)
This study aims to analyze shoreline changes numerically in the Batu Karas Beach area, Pangandaran, using the one-line model approach. This model is used to predict shoreline shifts resulting from abrasion and sedimentation processes influenced by wave and current dynamics. The simulation method employed is the finite difference method, which simplifies the problem of shoreline movement into a dominant one-dimensional form. Simulation results show that in several segments of the beach, abrasion occurs at an average rate of 35.94 meters per year, while in other segments, accretion occurs at a rate of 34.32 meters per year. These findings provide important insights into coastal dynamics that can be used to support sustainable coastal management and protection planning.